Rapidly Progressing Visual Loss Associated with Optic Nerve Head Drusen: Is there A Role For Lowering Intraocular Pressure? - El-Assal Karim; J. Tatham Andrew (Journal of Ophthalmic Science, 2016)
Background: Optic nerve head drusen are acellular hyaline deposits located anterior to the lamina cribrosa, frequently associated with visual field defects. Sometimes rapid worsening of vision may occur due to complications such as acute vascular events, choroidal neovascularization, or serous maculopathy. Case Presentation: Although there are no proven treatments for Optic nerve head drusen associated field loss, we present the case of a patient with Optic nerve head drusen and bilateral rapid progression of visual field loss that has stabilized on intraocular pressure lowering medication. This suggests a role for IOP-mediated retinal ganglion cell loss in this individual. The mechanism of progressive Optic nerve head drusen associated field loss is poorly understood, however experimental glaucoma models and human in vivo imaging studies have shown that structural differences within the optic nerve head are likely to contribute to individual susceptibility to IOP-mediated damage. Conclusion: We propose that eyes with Optic nerve head drusen may be less able to dampen IOP mediated stress, contributing to loss of retinal ganglion cells in some patients.
Keywords: Optic nerve head drusen